Pemenuhan Hak atas Air Bersih dan Sehat, Serta Hak Menggugat Masyarakat - Josina Augusthina Yvonne Wattimena (Balobe Law Journal, 2021)
Introduction: Clean and healthy water is the right of everyone to get and enjoy it. The fact is that not everyone can enjoy this right, and this is closely related to the obligations of the State. This State obligation should be implemented in various actions as a form of fulfillment of human rights. Purposes of the Research: Analyze and study the fulfillment of the right to clean and healthy water and the right to sue the community.Methods of the Research: This research is an empirical research with interview and questionnaire data which are then processed qualitatively. Results / Findings of the Research: The results showed that the right to clean and healthy water has very broad dimensions, two of which contain a health dimension but also an environmental dimension, which is essentially a human right. Therefore, regulations on the fulfillment of the right to clean and healthy water have been formulated in various legal provisions, both law making treaties and soft law. National law such as the 1945 Constitution of the Republic of Indonesia has formulated and implemented it has been followed by various implementing regulations. The full exercise of the right to clean and healthy water which is demanded by the ICESCR depends entirely on appropriate legal provisions and legal remedies at the national level.